Pelatihan Manajemen Pengelolaan Keuangan Ekonomi Mikro Desa Ngingas Rembyong Kecamatan Sooko Kabupaten Mojokerto - Rubiyanto, Rubiyanto; Setiono, Hari (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The presence of BUMDes is expected to be able to drive the micro business sector in the village because the micro business sector is an economic milestone for the village community. The development of micro businesses that are appropriate to become business actors that have competitiveness, then micro businesses should be directed more towards the resilience of business actors in facing competitiveness and increasing productivity. of course these efforts must be supported with sufficient capital and financial management capabilities. Management of the financial statements of micro business operators that are still simple makes it difficult to detect any gains or losses in their business. This is because their financial management is still mixed between business finance and personal finance. the micro business actors still do not understand the issue of good financial management, in order to make business policies based on the financial statements.